Segurança hídrica: análise bibliométrica da produção científica global e Brasileira - Volmar, Livinson (2022)
The concern about water resources is increasing due to lower water availability and increased demand. Given this, Water Security (WS) was created to improve the insurance of these resources and also protect against the impacts caused by climate change. Being a multidisciplinary parameter, it is likely to be applied to any region of the world, which is why scientific production on it has grown over the years. According to the UN, SH is about ensuring sustainable access to water of adequate quantity and quality, the maintenance of livelihoods, human well-being, and socio-economic development, as well as to ensure protection against water pollution and water-related disasters and the preservation of ecosystems. Thus, the present research brings a bibliometric analysis of the theme ‘‘Water Security’’, which is present in the main collection of the Web of Science. In fact, this thematic represents a total of 965 publications distributed in the period between 1993 a 2022. By investigating the available information, in which the term ‘‘water security index’’ was contained in its titles, only documents of the type and articles, conference article, review articles, and early access article were considered in the study. As an analysis tool, two software packages were used: the Biblioshiny application, which can be accessed through the Bibliometrix package of R, and VOSviewer. The results were them analyzed at the level of authors, sources, and documents regarding the number of publications, total citations, impact indexes, collaboration networks, and the occurrence of keyword. From this, it was concluded that the results found demonstrate that in the last decade, studies related to this area, show that there is a great interest of the scientific community on the subject in the world. In view of the above, water security depends on several variables such as availability, quality, and external factors, among them climate forcing and anthropogenic pressure. Water governance must therefore integrate human needs and the functioning of ecosystems, taking into account climatic uncertainties and pollution, in order to advance better planning of Brazilian and global water resources.